1989
DOI: 10.1007/bf00001319
|View full text |Cite
|
Sign up to set email alerts
|

Soil N mineralization and nitrification in relation to nitrogen solution chemistry in a small forested watershed

Abstract: Abstract. Spatial variations in soil processes regulating mineral N losses to streams were studied in a small watershed near Toronto, Ontario. Annual net N mineralization in the 0-8cm soil was measured in adjacent upland and riparian forest stands using in situ soil incubations from April 1985 to 1987. Mean annual rates of soil N mineralization and nitrification were higher in a maple soil (93.8 and 87.0 kg.ha-' ) than in a pine soil (23.3 and 8.2 kgha-I). Very low mean rates of mineralization (3.3 kg.ha-' ) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
2

Year Published

1990
1990
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 24 publications
3
36
2
Order By: Relevance
“…Soil solution concentrations of NO 3~-N and NO 3~-N plus NH 4 + -N correlated well with all rates of N transformations, with the exception of buried bag nitrification (Table 1). Previous research has also shown that soil solution collections are good indicators of N availability and potential leaching losses (Hansen and Harris, 1975;Montagnini et al, 1986;Hill and Shackleton, 1989). Net mineralization measurements were also correlated with soil inorganic N content at the time of sampling, with r values ranging from 0.28 to 0.60 (Table 1).…”
Section: Treatment Effect Discriminationmentioning
confidence: 64%
See 1 more Smart Citation
“…Soil solution concentrations of NO 3~-N and NO 3~-N plus NH 4 + -N correlated well with all rates of N transformations, with the exception of buried bag nitrification (Table 1). Previous research has also shown that soil solution collections are good indicators of N availability and potential leaching losses (Hansen and Harris, 1975;Montagnini et al, 1986;Hill and Shackleton, 1989). Net mineralization measurements were also correlated with soil inorganic N content at the time of sampling, with r values ranging from 0.28 to 0.60 (Table 1).…”
Section: Treatment Effect Discriminationmentioning
confidence: 64%
“…J. 59: (1995 1990; Hart and Firestone, 1989;Hill and Shackleton, 1989). However, these comparisons were limited by the number of methods tested or by the sites on which they were tested.…”
mentioning
confidence: 99%
“…Perhaps the least anticipated finding was that ␦ 13 C and ␦ 15 N values exhibited significant year-to-year variation. The cause of this temporal fluctuation is unknown, but ␦ 15 N values of feathers may be indirectly influenced by factors such as soil nitrogen dynamics (38,39), water availability (40)(41)(42)(43)(44), and plant nitrogen storage strategies (45)(46)(47)(48)(49) that affect the isotopic composition of C 3 -based food webs. These processes are controlled to varying degrees by climatological parameters such as rainfall and temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Nadelhoffer, Raison, Connell & Khanna, 1987;Adams et al, \9?,9a,b;Hill & Shackleton, 1989;Polglase, Attiwill & Adams, 1992 a). The rate of net mineralization of nitrogen is about equal to the rate of nitrogen return in above-ground litterfall over a range of eucalypt forests (Adams et al, 1989a;Polglase et al, 1992a).…”
Section: {B) Rates Of Mineralization In Forestsmentioning
confidence: 99%